A series of 38 novel germline and somatic mutations of NIPBL in Cornelia de Lange syndrome. Issue 5 (3rd February 2016) - Nizon, M.; Henry, M.; Michot, C.; Baumann, C.; Bazin, A.; Bessières, B.; Blesson, S.; Cordier‐Alex, M.‐P.; David, A.; Delahaye‐Duriez, A.; Delezoïde, A.‐L.; Dieux‐Coeslier, A.; et al.
Abstract : Cornelia de Lange syndrome is a multisystemic developmental disorder mainly related to de novo heterozygous NIPBL mutation. Recently, NIPBL somatic mosaicism has been highlighted through buccal cell DNA study in some patients with a negative molecular analysis on leukocyte DNA. Here, we present a series of 38 patients with a Cornelia de Lange syndrome related to a heterozygous NIPBL mutation identified by Sanger sequencing. The diagnosis was based on the following criteria: (i) intrauterine growth retardation and postnatal short stature, (ii) feeding difficulties and/or gastro‐oesophageal reflux, (iii) microcephaly, (iv) intellectual disability, and (v) characteristic facial features. We identified 37 novel NIPBL mutations including 34 in leukocytes and 3 in buccal cells only. All mutations shown to have arisen de novo when parent blood samples were available. The present series confirms the difficulty in predicting the phenotype according to the NIPBL mutation. Until now, somatic mosaicism has been observed for 20 cases which do not seem to be consistently associated with a milder phenotype. Besides, several reports support a postzygotic event for those cases. Considering these elements, we recommend a first‐line buccal cell DNA analysis in order to improve gene testing sensitivity in Cornelia de Lange syndrome and genetic counselling.